Media portrayal of Donald Trump in the Post-2024 United States Presidential Election: a content analysis of news reports and opinion columns in The Star Online, Malaysia - Lim, Lai Hoon (Penerbit Universiti Kebangsaan Malaysia, 2025)
The way the media constructs events and personalities often have a significant impact on how the public perceives political figures. When President Donald Trump took the limelight in international politics during the 2024 U.S. presidential election and once again became a polarising figure, it turned out to be a significant topic of scholarly inquiry. Donald Trump’s post-election actions and statements have attracted momentous attention of global media outlets, including The Star Online, a prominent Malaysian English-language mainstream news outlet. By using the Framing Theory, this study examined Donald Trump’s portrayal in the aftermath of the 2024 U.S. presidential election to determine the themes, tones, and sources in that coverage. News reports and opinion columns published in the first 100 days were content analysed to probe into how The Star Online presents and contextualises news and opinions on Trump for Malaysian audiences. The findings suggested that The Star Online primarily portrayed Trump in a negative light. The reports focused on Trump’s policies, authoritarian leadership style, nationalism, and controversial statements after the election. The Star Online primarily framed dominant themes as criticism, including Trump’s economic policies, immigration stance, and foreign relations. The Star Online relied predominantly on international wire agencies as news sources, which indicates that the local media outlets may correspond with international media viewpoints, offering a homogeneous portrayal of Donald Trump.